Righteous anger in contemporary Italian literary and cinematic narratives - Lucamante, Stefania (Toronto Italian studies., 2020)
"Righteous Anger in Contemporary Italian Literary and Cinematic Narratives analyses the role of passion--particularly indignation--and how it shapes intention and inspires the work of many contemporary Italian writers and filmmakers. Noting how art often holds the power to shed light on issues surrounding inequity, inequality, and injustices, the book explores the ethical function of art as a tool in resistance and sociopolitical protest, thereby validating the axiom that ethics and aesthetics can still collaborate in the creation of meaning. Drawing on a range of Italian novels and films and examining the works of artists such as Tiziano Scarpa, Simona Vinci, Paolo Sorrentino, and Monica Stambrini, the author shows that anger can be used constructively as a weapon of resistance against negative and oppressive forces."--